Zur Kenntnis von Sitona regensteinensis Herbst (Coleoptera: Curculionidae). 2. Mitteilung. - Scherf, Heinz (Contributions to Entomology = Beiträge zur Entomologie, 1958)
In the present part II of researches on the biology of Sitona regensteinensis Hbst. explanations are made on the morphology of first instar larva, of full grown larva, and of the pupa. This stages were till now unknown. Besides the habits of the larvae are described. The development takes place at the roots of Sarothamnus scoparius. Many losses occur among first instar larva during the way on their food-locality, and this is the main cause that in spite of the large numbers of eggs only few full grown larvae and later on weevils on the bushes are found.